Strategi Pengelolaan Akun Tiktok Edukatif: Studi Kasus Pada Akun Tiktok @Buiramira - Ananda Maharani; Asep Suryana; Teddy Kurnia Wirakusumah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research aims to investigate the management strategies of the educational TikTok account @buiramira from the planning, implementation and activation stages, to the optimization of the management of the educational TikTok account @buiramira. This study is a qualitative research employing a descriptive case study method. The results of this research are to determine the social media management strategy carried out by the educational TikTok account @buiramira. There are three strategies involved in the process. First, in the planning stage, Mrs Ira identifies target audiences, analyzes their needs and interests, and sets goals for content creation. Next, in the activation and monitoring stage, Mrs Ira prepares equipment for content creation, followed by editing processes, ensuring the quality of content, and evaluating the production results, culminating in scheduling content publication. Finally, in the evaluation stage, Mrs Ira assesses the production results again, and upon uploading content, evaluates its performance.